Dimethylarsinic acid is the causal agent inducing rice straighthead disease. (15th May 2020) - Tang, Zhong; Wang, Yijie; Gao, Axiang; Ji, Yuchen; Yang, Baoyun; Wang, Peng; Tang, Zhu; Zhao, Fang-Jie
Abstract: Straighthead disease is a physiological disorder in rice with symptoms of sterile spikelets, distorted husks, and erect panicles. Methylated arsenic species have been implicated as the causal agent of the disease, but direct evidence is lacking. Here, we investigated whether dimethylarsinic acid (DMA) causes straighthead disease and its effect on the transcriptome of young panicles. DMA addition caused typical straighthead symptoms in hydroponic culture, which were alleviated by silicon addition. DMA addition to soil at the tillering to flowering stages induced straighthead disease. Transgenic rice expressing a bacterial arsenite methyltransferase gene gained the ability to methylate arsenic to mainly DMA, with the consequence of inducing straighthead disease. Field surveys showed that seed setting rate decreased with increasing DMA concentration in the husk, with an EC50 of 0.18 mg kg −1 . Transcriptomic analysis showed that 364 and 856 genes were significantly up- and down-regulated, respectively, in the young panicles of DMA-treated plants compared with control, whereas Si addition markedly reduced the number of genes affected. Among the differentially expressed genes, genes related to cell wall modification and oxidative stress responses were the most prominent, suggesting that cell wall metabolism is a sensitive target of DMA toxicity and silicon protects against this toxicity. Abstract : Dimethylarsinic acid causes straighthead disease in rice, with cell wall metabolism as a sensitive target of toxicity.